Middle Eastern Immigrants’ Satisfaction With Malaysian Healthcare - Khalid, Haliyana; Anis, Mohamad Saleem; Rizal, Adriana Mohd (Business Management and Strategy, 2021)
There has been an increasing number of Middle Eastern immigrants arriving in Malaysia over the last decade due to political and economic instability in their countries. Given their somewhat ambiguous living conditions and residence status here (e.g. legal, illegal, refugee, etc.), it is imperative to understand their situation in-depth. One of the most important aspects that impact the living conditions of these immigrants is health; accordingly, in this research, we attempted to discover the extent and factors of Middle Eastern immigrants’ satisfaction with the Malaysian healthcare system and its facilities. In this cross-sectional study, we used a questionnaire to collect data from 219 respondents both online and in-person. Various statistical methods were employed to analyze the data, including descriptive analysis, Pearson’s correlation, and multiple regression. The findings indicate a slight dissatisfaction among Middle Eastern immigrants with respect to the Malaysian healthcare system, due to the cost of health services and communication barriers. The results also highlight that marital status, monthly income, awareness of services, Malay language proficiency, and culture are factors that impact immigrants’ perception of the quality of healthcare services. Therefore, this study provides valuable insights into this important group of immigrants in terms of their experience in public and private healthcare facilities that shape their opinions and satisfaction with the Malaysian healthcare system.